Meningkatkan Kemandirian Anak Kelompok B Melalui Metode Sosiodrama - Sri Narni (Education Reserach Center, 2025)
This study aims to improve the independence of children in Group B at TK Negeri Pembina Surabaya through the implementation of the Sociodrama method. The initial observation revealed that most children were still at the Not Yet Developed (BB) level of independence, indicating a high dependency on adults for daily activities. The research was conducted using the Classroom Action Research (CAR) approach in two cycles, each consisting of planning, action, observation, and reflection. The focus was on increasing children's independence through role-playing activities that allow them to experience various roles and develop their confidence, emotional regulation, and social skills. The results of this study showed a significant improvement in children's independence after the implementation of the Sociodrama method. In the initial phase, none of the 18 children reached the Very Well Developed (BSB) criterion. After the first cycle, although there was a positive shift, no children had yet achieved the BSB criterion. However, following the second cycle, all 18 children, or 100%, reached the Very Well Developed (BSB) level. This indicates that children have successfully developed independent behaviors such as speaking up in class, choosing activities independently, interacting positively with peers, sharing, helping each other, taking turns, and following class rules. The success of this study is attributed to the effective collaboration between researchers and teachers, the use of varied media relevant to children's interests, and the consistent provision of motivation and rewards. The findings suggest that the Sociodrama method not only effectively enhances children's independence but also creates a stimulating and engaging learning environment. This study concludes that innovative and structured approaches like Sociodrama can significantly impact the development of independence and social skills in early childhood education. The results of this research are expected to serve as a valuable reference for educators, researchers, and practitioners in the field of early childhood education to continue innovating and fostering children's potential